2014
DOI: 10.1016/j.metabol.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin, a sodium glucose co-transporter 2 inhibitor, reduces post-meal glucose excursion in patients with type 2 diabetes by a non-renal mechanism: results of a randomized trial

Abstract: These findings suggest that a non-renal mechanism (ie, beyond UGE) contributes to glucose lowering for canagliflozin 300 mg, but not 150 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 16 publications
3
37
0
1
Order By: Relevance
“…7) [36]; similar results were observed in other phase I, [11], phase II [39], and phase III studies [40,41]. An additional non-renal effect contributing to postprandial glucose lowering in patients with T2DM (as observed in healthy participants) treated with canagliflozin 300-mg dose before a meal was observed; this effect was not observed with a 150-mg dose [42].…”
Section: Plasma Glucose In Patients With T2dmsupporting
confidence: 80%
“…7) [36]; similar results were observed in other phase I, [11], phase II [39], and phase III studies [40,41]. An additional non-renal effect contributing to postprandial glucose lowering in patients with T2DM (as observed in healthy participants) treated with canagliflozin 300-mg dose before a meal was observed; this effect was not observed with a 150-mg dose [42].…”
Section: Plasma Glucose In Patients With T2dmsupporting
confidence: 80%
“…This was reported first in healthy volunteers 53 but has since been reported in a study of people with type 2 diabetes. 54 Because these drugs act through an insulin-independent mechanism, they can be effective when other drugs that depend entirely (sulfonylureas and meglitinides) or in part (gliptins and GLP-1 analogues) on stimulating insulin release have lost effectiveness. In type 2 diabetes, the capacity of the pancreatic beta cells to produce insulin often falls over time.…”
Section: Sodium-glucose Co-transporter 2 Inhibitorsmentioning
confidence: 99%
“…A study by Stein et al 54 from Janssen Research and Development looked at the SGLT1 effect in people with type 2 diabetes and found that canagliflozin 300 mg, but not 150 mg, reduced postprandial PG, by about 0.5 mmol/l (from graph) for about 2 hours after administration, as it depends on an intestinal drug action not a systemic one. Hence this reduction would occur only after the single daily dose.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…Notably, in the current study, we used 100 mg of canagliflozin once a day unlike the previous clinical study in healthy subjects in which 300 mg once a day was used [9] because only this dose is approved in Japan. Stein et al reported that a dose above 150 mg is needed to reduce plasma postprandial glucose via a non-renal mechanism (probably via inhibiting glucose absorption in the small intestine) in patients with type 2 diabetes [20]. We speculate that the reason for our positive results with this dose of canagliflozin is based, at first, on the difference in the background of patients such as race, BMI, and state of glycemic control as reflected by baseline HbA1c levels.…”
Section: Discussionmentioning
confidence: 73%